Celiac Disease Causes Epithelial Disruption and Regulatory T Cell Recruitment in the Oral Mucosa - Sanchez-Solares, Javier; Sanchez, Luis; Pablo-Torres, Carmela; Diaz-Fernandez, Celso; Sørensen, Poul; Barber, Domingo; Gomez-Casado, Cristina (Frontiers in Immunology, 2021)
Celiac disease (CD) is a chronic autoimmune disease characterized by an immune-triggered enteropathy upon gluten intake. The only current treatment available is lifelong Gluten Free Diet (GFD). Several extraintestinal manifestations have been described in CD, some affecting the oral mucosa. Thus, we hypothesized that oral mucosa could potentially be a target for novel biomarkers and an administration route for CD treatment. 6 de novo diagnosed and 7 CD patients under GFD for at least 1 year were recruited. Non-celiac subjects (n=8) were recruited as control group. Two biopsies of the cheek lining were taken from each subject for mRNA analysis and immunohistochemical characterization. We observed a significant decrease in the expression of epithelial junction proteins in all CD patients, indicating that oral mucosa barrier integrity is compromised. FoxP3+ population was greatly increased in CD patients, suggesting that Tregs are recruited to the damaged mucosa, even after avoidance of gluten. Amphiregulin mRNA levels from Peripheral Blood Mononuclear Cells (PBMCs) and epithelial damage in the oral mucosa correlated with Treg infiltration in all the experimental groups, suggesting that recruited Tregs might display a “repair” phenotype. Based on these results, we propose that oral mucosa is altered in CD and, as such, might have diagnostic potential. Furthermore, due to its tolerogenic nature, it could be an important target for oral immunotherapy.